Isolation and characterization of the human tyrosine aminotransferase gene. - Rettenmeier, R (1990)
Structure and sequence of the human gene for tyrosine aminotransferase (TAT) was determined by analysis of cDNA and genomic clones. The gene extends over 10.9 kbl and consists of 12 exons giving rise to a 2,754 nucleotide long mRNA (excluding the poly(A)tail). The human TAT gene is predicted to code for a 454 amino acid protein of molecular weight 50,399 dalton. The overall sequence identity within the coding region of the human and the previously characterized rat TAT genes is 87% at the nucleotide and 92% at the protein level. A minor human TAT mRNA results from the use of an alternative polyadenylation signal in the 3' exon which is present but not used at the corresponding position in the rat TAT gene. The non-coding region of the 3' exon contains a complete Alu element which is absent in the rat TAT gene but present in apes and old world monkeys. Two functional glucocorticoid response elements (GREs) reside 2.5 kb upstream of the rat TAT gene. The DNA sequence of the corresponding region of the human TAT gene shows the distal GRE mutated and the proximal GRE replaced by Alu elements.